2008
DOI: 10.1016/j.fertnstert.2007.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and cellular adiponectin in polycystic ovary syndrome: relationship to glucose tolerance and insulin action

Abstract: Both circulating adiponectin levels and the portion present as the most active HMW form are reduced in PCOS, with differences related to the degree of glucose intolerance and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 45 publications
7
31
1
Order By: Relevance
“…The presence of multiple bands following electrophoresis under nonreducing conditions (Fig. 3) is in agreement with our previous work (2,4,19) and that of Waki et al (36).…”
Section: Subject Characteristicssupporting
confidence: 92%
“…The presence of multiple bands following electrophoresis under nonreducing conditions (Fig. 3) is in agreement with our previous work (2,4,19) and that of Waki et al (36).…”
Section: Subject Characteristicssupporting
confidence: 92%
“…A recent study also showed that adiponectin levels are related to the degree of glucose intolerance and IR (31). However, in the present study, adiponectin level was not associated with IR markers, except for fasting glucose (r = -0.35, P < 0.05).…”
Section: Discussioncontrasting
confidence: 82%
“…According to the effects of excess adiposity and IR on adiponectin levels, a marked decrease of adiponectin levels in women with PCOS can be assumed. This assumption has been confirmed by the findings of numerous studies (24,25). As mentioned above, both MetS and PCOS are related with low adiponectin levels and it is expected that women with concomitant PCOS and MetS would have lower adiponectin levels compared to women with PCOS only.…”
Section: Discussionsupporting
confidence: 62%